An assessment of financial and management challenges faced by community advice offices in the Western Cape Province - Nyapisi, Thabiso (Department of Social Development, 2014)
The period between 1960s ? 1980s saw emergence and proliferation of Community Advice Offices (CAOs) in South Africa as a response to the injustices of the apartheid regime. These small community-based organisations became crucial institutions within communities as they voiced out against discriminatory apartheid policies practised in marginalized communities at the time. So, CAOs continued to provide much-needed paralegal advice and information to members of the communities. Although the dawn of democratic South Africa presented the hope of benefits including that of access to human rights and legal assistance, the majority of South Africans still struggle to enjoy such social fruits. Thus, accessing some of those benefits has remained a challenge for the poor and those living in rural areas. Today, CAOs continue to provide paralegal assistance and information on social problems such as social grants, housing, debt, eviction, unemployment, domestic violence, pension, family matters, and labour-related matters, among others. This study was an empirical research that aimed to explore the financial and management challenges faced by CAOs in the Western Cape Province. This study employed a qualitative research approach and data was collected through conducting in-depth interviews with the directors of the CAOs ? as respondents. A purposive sampling technique was adopted and a sample of 20 organisations participated in this research. This research found that eighty per-cent (80%) of the research participants maintained that their organisations were not financially secure. The majority of the respondents indicated that government should 'come to the party' and financially support their organisations in a much more significant and sustainable way as they (75% of the respondents) felt that they were doing work for government. On the management side, only 45% of the respondents indicated that their Board of Directors were fully involved in the running of the organisations and most of CAOs failed to attract volunteers as they could not afford to give them stipends. The majority of the research participants felt that CAOs should be recognised and paralegals be included in the current Legal Practice Bill [B 20 - 2012] because failure to do so would leave the majority of South African citizens, living in poor communities, outside of access to the law.